دور أبعاد المرونة الاستراتيجية في تحقيق متطلبات التكيف الاستراتيجي دراسة تحليلية في عينة من الشركات التجارية في مدينة زاخو- العراق - يوسف, أ.م.د.ميهفان شريف (Sulaimani Journal for Humanities, 2021)
The current research aimes to investigate the role of strategic flexibility dimensions on achieving strategic adaptation requirements in commercial companies. The research depends on a set of main. and sub hypothetical which practically tested in commercial companies in Zakho city, and included (60) employees in understudy companies. The data were collected by using a questionnaire accomplished for this purpose, and it were analyzed statistically by consulting the SPSS program (version 25), to analyse correlations and effects relation between the research variables. The research came to a number of conclusions, the most important one is the presence of a positive correlation between strategic flexibility dimensions and strategic adaptation. Further, exists a moral effect of strategic flexibility dimensions in achieving strategic adaptation, in the light of conclusions, some points were suggested, the most important one is the necessity of promoting and maintaining the availability of high levels of strategic flexibility dimensions, and exploiting them to enhance the ability of achieving strategic adaptation requirements.
Keywords: Concept of strategic flexibility; strategic flexibility dimensions; concept of strategic adaptation